2021
DOI: 10.1128/msystems.00608-20
|View full text |Cite
|
Sign up to set email alerts
|

Host Immunity Alters Community Ecology and Stability of the Microbiome in a Caenorhabditis elegans Model

Abstract: Here, we used a Caenorhabditis elegans microbiome model to demonstrate how genetic differences in innate immunity alter microbiome composition, diversity, and stability by changing the ecological processes that shape these communities. These results provide insight into the role of host genetics in controlling the ecology of the host-associated microbiota, resulting in differences in community composition, successional trajectories, and response to perturbation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The results of this survey were then used to choose a subset of mutants for further analysis. The considered mutants either showed impaired immunity or impaired microbial uptake which potentially influences microbiota abundance [27,28,49,66]. We found that MYb11 colonisation was significantly higher in the mutants dbl-1, sma-6, phm-2, tnt-3 , and tir-1 compared to the wildtype N2 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this survey were then used to choose a subset of mutants for further analysis. The considered mutants either showed impaired immunity or impaired microbial uptake which potentially influences microbiota abundance [27,28,49,66]. We found that MYb11 colonisation was significantly higher in the mutants dbl-1, sma-6, phm-2, tnt-3 , and tir-1 compared to the wildtype N2 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 96%
“…In nature, the nematode is associated with a species-rich microbiota [45,46], which includes immune-protective microbes, such as a variety of Pseudomonas species [47,48]. Moreover, innate immunity [27,28,49] and microbe-microbe interactions have been shown to influence C. elegans microbiota composition and function [46,50]. For the current study, we used different C. elegans mutants, which either affect the nematode’s immune system (e.g., p38 MAPK and TGF- β signalling) or microbial colonisation (i.e., through disruption of the grinder in the nematode’s pharynx).…”
Section: Introductionmentioning
confidence: 99%
“…Indicated sets of CFU/worm data were previously published, and data and methods are available from the indicated manuscript (Taylor and Vega 2021).…”
Section: Methodsmentioning
confidence: 99%
“…'Common garden' experiments, in which different C. elegans strains and related species were raised in identical compost microcosms, identified a significant contribution of host genetics to determining microbiome composition (17). Subsequent studies identified conserved regulatory pathways, including insulin/insulin-like (IIS) signaling (18,19) and the DBL-1/BMP pathway (12), as contributing to shaping of the gut microbiome. DBL-1 signaling further came to the forefront as a mechanism that controls a specific subset of gut bacteria, which has the potential to cause detrimental effects when control was impaired (12).…”
Section: Introductionmentioning
confidence: 99%